PERSISTENT ST SEGMENT ELEVATION/DEPRESSION IN MYOCARDIAL INFARCTION PATIENTS AND ITS VALUE IN PREDICTING SHORT-TERM POST-HOSPITAL OUTCOMES - S. V. Semakina; R. T. Saygitov; M. G. Glezer (Российский кардиологический журнал, 2010)
Electrocardiography is the most accessible and widely used method for diagnosing myocardial infarction (MI) and predicting MI outcomes. This paper presents the results of the prospective study, assessing ST segment dynamics in 248 MI patients and evaluating its role in predicting short-term (3 months) post-hospital MI outcomes. At least once (at admission, at Days 6-8, or at discharge), ST segment elevation was registered in 117 MI patients (47%), and ST segment depression – in 134 (54%). Among these participants, persistent ST elevation/depression, registered at all control points, was observed only in 15%: two thirds (26 out of 37) had persistent ST elevation, and the others – persistent ST depression. During the three-month follow-up period, a combined endpoint (cardiovascular death, non-fatal MI, stroke, or unstable angina) was registered in 48 participants (19,7%; the endpoint was evaluated in 245 patients with known post-hospital outcomes). Independent predictors of poor post-hospital MI prognosis included persistent ST elevation (odds ratio 2,9; 95% confidence interval 1,2-7,0) and persistent ST depression (odds ratio 4,3; 1,2-14,8), but not episodic, non-persistent ST elevation/depression.